Nymphaea alba var. rubra Lönnr. (Nymphaeaceae): a new record for the aquatic flora of Kashmir Himalaya, India - Afrozah Hassan; Shugufta Rasheed; Anzar A. Khuroo; Ather Masoodi; Irshad A. Nawchoo (Check List, 2020)
Nymphaea alba var. rubra Lönnr. is reported for the first time from Dal Lake, Kashmir Himalaya, India. The taxonomic identification was confirmed based on rhizome, leaf and flower characters. A brief description and photographic illustrations of N. alba var. rubra are provided to validate the new distribution record for aquatic flora of this Himalayan region. A comparison of N. alba var. rubra with its allied taxon, N. alba var. alba, is provided to facilitate field identification.